Common bile duct exploration with transpapillary stenting versus T-tube drainage for management of irretrievable common bile duct stones - Ahmed M Hassan; Ahmed Q Mohammed; Muhammad Abd El-Gawad Shawky (Wolters Kluwer Medknow Publications, 2017)
Background Common bile duct (CBD) stones are present in 10-18% of patients undergoing cholecystectomy for chronic calcular cholecystitis. Treatment of CBD stones is still controversial. However, CBD stones can be treated by cholecystectomy plus CBD exploration or by precholecystectomy or postcholecystectomy endoscopic retrograde cholangiopancreatography (ERCP) in two stages. If CBD exploration is performed and biliary decompression is needed after stone removal, the placement of transpapillary stent (TS) shows promising results in avoiding T-tube-related complications. Aim We aimed to evaluate the efficacy and complications of two approaches used for the management of CBD stones: intraoperative transpapillary CBD stent and T-tube external biliary drainage. Patients and methods Between May 2015 and May 2016, 24 patients underwent CBD exploration for treatment of irretrievable CBD stones. Included patients were randomly subjected to either CBD TS or T-tube drainage for management of irretrievable CBD stones after failure of ERCP. Results CBD exploration and TS placement (15 patients) was achieved either by a choledochotomy or through the cystic duct. There was no mortality in our series. Patients with a T-tube external biliary drainage (nine patients) had more surgery-related complications and a longer hospital stay. Postoperative ERCP to remove the CBD stent was successful in all cases. Conclusion Surgical transpapillary CBD stenting seems to be an effective method for management of irretrievable CBD stone with less surgical-related complications and less hospital stay and should be the first option in management of such patients.